2000
DOI: 10.1046/j.1439-0442.2000.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic and Cardiopulmonary Effects of Balanced Anaesthesia with Medetomidine–Midazolam and Butorphanol in Dogs

Abstract: The anaesthetic and cardiopulmonary effects of combinations of medetomidine (Me), midazolam (Mi) and butorphanol (Bu) were evaluated in dogs. The characterization of anaesthetic effects was assessed using a scoring system. The combinations tested were 20 or 40 micrograms/kg Me and 0.5 mg/kg Mi (20Me-Mi or 40Me-Mi) followed by either an intravenous injection of physiological saline solution (PSS) or Bu (0.1 or 0.3 mg/kg). The mixture of Me and Mi was injected intramuscularly, followed 15 min later by an intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…However, in P2 group the level of analgesia was graded as good (Table 1). Anaesthesia with adequate analgesic effect has been achieved by addition of 0.1 mg/kg butorphanol to medetomidine-midazolam anaesthesia in dogs (Itamoto et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…However, in P2 group the level of analgesia was graded as good (Table 1). Anaesthesia with adequate analgesic effect has been achieved by addition of 0.1 mg/kg butorphanol to medetomidine-midazolam anaesthesia in dogs (Itamoto et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Butorphanol, a synthetic opioid agonistantagonist, is used as an analgesic drug in veterinary medicine [11]. The combination of medetomidine, midazolam, and butorphanol has been reported as a safe and reliable anesthetic drug in the dog [13,26], sea lion [24] and red fox [2]. However, there are no reports in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the effect of combinations of ketamine and xylazine depends on the quantities of ketamine and xylazine [1,4]. On the other hand, the combination injectable agent (M/M/B) was determined by reports that were examined concerning other animal species [2,13,24,26], and the concentration of M/M/B (0.3/4/5 mg/kg) was determined by a preliminary experiment. The induction time of K/X: 80/8 was less than 5 min, and that of M/M/B: 0.3/4/5 was also less than 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os aumentos significativos da PAS em alguns momentos, neste grupo, evidenciam resultados anteriores (HELLYER et al, 1989). Em cães, a administração de benzodiazepínicos, opióides e agonistas adrenérgicos alfa-2 pode resultar em hipertensão arterial (GROSS et al, 1990;ITAMOTO et al, 2000). A administração de medetomidina e butorfanol em cães atropinizados promoveu aumento da pressão arterial, entretanto este aumento decresceu prontamente aos valores normais após a administração de cetamina, (TOMIZAWA et al, 1997).…”
Section: Discussionunclassified